Effect of dilute concentrations of Sm on the temperature‐dependent electrical and dielectric properties of ZnO. Issue 9 (14th April 2018) - Arora, Deepawali; Asokan, Kandasami; Kumar, Sunil; Kaur, Simranpreet; Kaur, Parvinder; Singh, Gurinder Pal; Mahajan, Aman; Kalia, Sameer; Kalia, Neerja; Seth, Kriti; Kaur, Puneet; Singh, Davinder P.
Abstract: Compounds of undoped and samarium (Sm) doped ZnO have been prepared by standard solid‐state reaction method. X‐ray diffraction (XRD), Williamson‐Hall (W‐H) analysis, Transmission Electron Microscopy (TEM), temperature‐dependent electrical and dielectric studies have been done to characterize these materials. Inclusion of Sm as dopant in hexagonal wurtzite ZnO changes the lattice parameters to a small extent with some Sm aggregation at higher concentration. Also, the mean particle sizes of ZnO:Sm compounds showed an inter‐correlation with the Scherrer method, W‐H analysis as well as with TEM results. The electrical resistivity depicts an exponential decay and metal‐semiconductor transition (MST) at ~300 K for the pristine sample whereas there is large decrement in the resistivity with Sm doping. The analysis of σac of ZnO suggests that the power law is obeyed and indicated an increase in the ac conductivity with Sm content. The mechanism behind this type of conductivity is elucidated by small polaron tunneling (SPT) model of conductivity. The dependence of ln dc on the temperature inverse shows that the traps of electrons are thermally activated such that low and high temperature activation energies confirm the presence of vacancies and interstitials of both O and Zn ions. Thus, a high value of dielectric constant makes these materials suitable for high frequency and charge storage device applications.